Normalization strategies for gene expression studies by real-time PCR in a marine fish species, Scophthalmus maximus - Urbatzka, R. (2018)
Thorough evaluation of normalization approaches is a fundamental aspect in real-time quantitative RT-PCR experiments to avoid artificial introduced intergroup variations. In our study, we tested three normalization strategies in an experimental data set derived from a toxicological exposure of Scophthalmus maximus to the peroxisome proliferator-activated receptor alpha (PPARα) agonist WY-14643. Juvenile turbots were exposed by repeated injections to 5. mg or 50. mg WY-14643/kg, and liver samples were taken at day 1, 7 and 21. Specifically, the mRNA expression of peroxiredoxin 5 (prdx5) was normalized to the cDNA content, to the mRNA expression of single reference genes (b-actin, b-act; elongation factor 1 α, ef1a; glyceraldehyde-3-phosphate dehydrogenase, gapdh; ribosomal protein L8, rpl8; tata-box binding protein, tbp; tubulin beta 2C chain, tubb2c; ubiquitin-conjugating enzyme E2L 3, ub2l3) or to a combination of multiple reference genes using geNorm, BestKeeper or NormFinder algorithms.Four single reference genes ( ef1a, rpl8, tubb2c, tbp) did not show any significant differences between the treatment groups over time, while significant intergroup variations were observed for cDNA content, gapdh, b-act and ub2l3. The normalization of prdx5 to the valid (not altered) single reference genes led to significant up-regulated ( prdx5/. rpl8), not-regulated ( prdx5/. ef1a; prdx5/. tbp) or down-regulated ( prdx5/. tubb2c) mRNA expression pattern. The multiple reference gene approaches resulted in different rankings and combinations of the most stable expressed reference genes (geNorm: ef1a>. rpl8>. b-act; BestKeeper: ub2l3>. gapdh>. ef1a; NormFinder: b-act>. ef1a). However, the normalization with the three multiple reference gene procedures demonstrated consistent expression pattern with a significant up-regulation of prdx5 in response to the higher concentration after 21. days.Concluding, even if not yet established as "gold" standard for expression profiling in environmental toxicology or physiology using freshwater or marine fish models, the multiple reference gene approach is recommended, since it eliminates any biased results, which represented the major flaw of single reference genes.